Tailoring co-doping of cobalt and nitrogen in a fullerene-based carbon composite and its effect on the supercapacitive performance. Issue 3 (23rd December 2021) - Jiang, Bohong; Zhang, Guangpu; Tang, Qin; Meng, Fancang; Zhou, Dechun; Zhao, Wenli; Jiang, Wei; Ji, Qingmin
Abstract : Controllable cobalt and nitrogen are in situ formed in mesoporous carbon composites via fullerene self-assembly and pyrolysis, which lead to an enhanced electrochemical performance. Abstract : Fullerene-based carbons have attracted great attention in applications of energy storage and conversion due to their unique properties and tunable architectures. However, fullerene's poor long-range conductivity limits their application performance for supercapacitors. Therefore, developing active fullerene-based carbons with high capacitances is expected. In this work, mesoporous carbon composites with various doping amounts of cobalt (Co) and nitrogen (N) were fabricated via manipulation of fullerene self-assembly with a cobalt tetramethoxy phenylporphyrin (CoTMPP) and pyrolysis. The confined state of CoTMPPs within the fullerene superstructures facilitates the fixation of Co and N during the carbonation and leads to a highly homogeneous distribution state within fullerene-based carbon composites. When used as electrodes for supercapacitors, the doped carbon composite showed significantly improved electrochemical performance. The specific capacitance could be nearly ten times higher than that of the fullerene carbons without doping and they have excellent cyclic stability. The work presents new insight into controllable functional doping of carbon materials. It may also further promote the development of fullerene superstructures for advanced electrochemical applications.